The Role of Job Satisfaction in Mediating PT X's Employee Turnover Intention Modeling Based on Work Environment and Work Overload - Kurniawan, Wahyu Indra; Tohari, Amin (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: This study aims to determine Job Satisfaction in mediating the variables of the work environment and workload of PT X employees on the employees' intention to leave work. Design/Method/Approach: This study uses the Explanatory quantitative method. . Research Findings: In the end, the Work Environment and Workload have a significant negative and positive effect on Turnover intention. The Work Environment has a positive and significant effect on Job Satisfaction while the Workload is not significant. However, for the mediation variable, it has no effect at all or cannot mediate. Theoretical/Originality Contribution: This study contributes empirical experience to the literature on the influence of work environment and workload on job satisfaction and turnover intention. These results emphasize the vital aspects of the work environment as a key factor in maximizing job satisfaction, providing new and relevant insights. Practice/Policy Implications: This study emphasizes that companies must create an environment of activities that are conducive to improving employee satisfaction. Additionally, effective workload management is essential to maintain employee well-being and reduce potential turnover intentions. Research limitations: Research is limited to one organization, so the results may be less generalizable. Further research is recommended to extend coverage to a wide range of organizations and industries, as well as use a qualitative approach to dig deeper into employee perceptions and experiences.